2003
DOI: 10.1016/s0092-8674(03)00552-x
|View full text |Cite
|
Sign up to set email alerts
|

S Phase Activation of the Histone H2B Promoter by OCA-S, a Coactivator Complex that Contains GAPDH as a Key Component

Abstract: We have isolated and functionally characterized a multicomponent Oct-1 coactivator, OCA-S which is essential for S phase-dependent histone H2B transcription. The p38 component of OCA-S binds directly to Oct-1, exhibits potent transactivation potential, is selectively recruited to the H2B promoter in S phase, and is essential for S phase-specific H2B transcription in vivo and in vitro. Surprisingly, p38 represents a nuclear form of glyceraldehyde-3-phosphate dehydrogenase, and binding to Oct-1, as well as OCA-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
446
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 488 publications
(468 citation statements)
references
References 33 publications
18
446
0
4
Order By: Relevance
“…Interestingly, it is clear now that GAPDH displays a distinct membrane, cytosolic and nuclear localization. In those subcellular sites, it is involved in a number of cellular functions, including endocytosis and membrane fusion (Glaser and Gross, 1995;Robbins et al, 1995), vesicular secretory transport (Tisdale, 2001), translational control (Yi et al, 2000), nuclear tRNA transport (Singh and Green, 1993), DNA replication (Zheng et al, 2003) and DNA repair (Krynetski et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it is clear now that GAPDH displays a distinct membrane, cytosolic and nuclear localization. In those subcellular sites, it is involved in a number of cellular functions, including endocytosis and membrane fusion (Glaser and Gross, 1995;Robbins et al, 1995), vesicular secretory transport (Tisdale, 2001), translational control (Yi et al, 2000), nuclear tRNA transport (Singh and Green, 1993), DNA replication (Zheng et al, 2003) and DNA repair (Krynetski et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These include the transcriptional regulation of histone gene expression (Zheng et al, 2003), the role of GAPDH in nuclear membrane fusion (Nakagawa et al, 2003), in the modulation of telomere structure (Sundararaj et al, 2004), in the recognition of fraudulent nucleotides in DNA arising from cancer chemotherapy (Krynetski et al, 2003) and in triggering apoptosis (Chuang et al, 2005;Hara et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The much greater decrease in GAPDH elicited by VPA in the ChIP complex than in the nuclear preparation of unstimulated CGC ( Figure 6 vs Figure 5b) suggests that only a small fraction of nuclear GAPDH is present with histone proteins in the ChIP complex. Interestingly, it was recently reported that the histone H2B promoter interacts with a GAPDHcontaining transcriptional coactivator complex, 31 indicating that nuclear GAPDH may have an important function in gene transcription. GAPDH also selectively interacts with the polyglutamate region of huntingtin, 32 a Huntington's disease protein that accumulates in the nuclei as the pathophysiology progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-and stress-activated protein kinase-1 (MSK1) can be directly activated by p38 and ERK, and may mediate activation of CREB [62][63][64]. p38 is also thought to regulate S phase activation of histone 2B (H2B) promoter through OCA-S, a component of p38 [65].…”
Section: Downstream Substrates Of P38 Group Map Kinases Protein Kinasmentioning
confidence: 99%